Turning environmental strategies into competitive advantage in the Malaysian manufacturing industry: mediating role of environmental innovation - Tze, San Ong; Lee, Ah Suat; Teh, Boon Heng (Universiti Putra Malaysia Press, 2021)
Turning environmental strategies into competitive advantage in the Malaysian manufacturing industry: mediating role of environmental innovation The environmental literature has focused on examining how firms leverage environmental innovation to convert environmental challenges into driving forces of competitive advantage. This paper enhances the knowledge on the implementation of environmental strategies in the Malaysian manufacturing industry by examining the impacts of environmental shared vision and environmental strategic focus on competitive advantage in the greening of the industry. The Smart PLS technique was used to analyse data collected from 124 Malaysian manufacturing firms on their environmental strategies as well as their implications for competitive advantage and environmental innovation. The findings suggest that environmental innovation mediates the positive exchange between firms’ environmental strategies and competitive advantage. The study provides valuable information for manufacturers in crafting their corporate competitive strategies, policies, and action plans. The direct and indirect roles of environmental innovation in fostering competitive advantage suggest that manufacturers should prioritise their environmental activities by enhancing innovation outcomes to achieve a successful green business status.